A Computational Model for Biological Tissues Considering the Influence of Injury on Growth and Remodelling. Issue 1 (18th November 2019) - Gierig, Meike; Marino, Michele; Wriggers, Peter
Abstract: Biological tissues adapt to changed loading conditions through growth and remodelling (G&R) to reestablish a so‐called homeostatic state. On the other hand, loading conditions above their physiological limits, as during trauma or surgical procedures, cause injury and can initiate pathological G&R. Herein, a modelling approach for G&R influenced by injury is presented combining the theories of plasticity and homogenised constrained mixtures. The results show that injury has a significant impact on the G&R behaviour and thus on the accomplishment of homeostasis.